2021
DOI: 10.1101/2021.03.19.434396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RNase III-mediated processing of atrans-acting bacterial sRNA and itscis-encoded antagonist

Abstract: Small RNAs (sRNAs) are emerging as important and diverse post-transcriptional gene expression regulators in bacterial stress responses and virulence. While originally identified mainly in intergenic regions, genome-wide approaches have revealed sRNAs encoded in diverse contexts, such as processed from parental transcripts by RNase E. Despite its well-known roles in rRNA processing, RNA decay, cleavage of sRNA-mRNA duplexes, the role of RNase III in sRNA biogenesis is less well understood. Here, we show that a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(20 citation statements)
references
References 109 publications
(200 reference statements)
1
19
0
Order By: Relevance
“…In our recent work, we showed that processed CJnc190 encoded in the CJnc190/180 sRNA locus of C. jejuni strain NCTC11168 represses ptmG translation by base‐pairing with its G‐rich translation initiation region using a single‐stranded C/U‐rich sequence within its second stem‐loop (SL2; Figure 1a; Svensson & Sharma, 2021). We noticed that the mature CJnc190 sRNA resembles the H. pylori sRNA RepG, which also uses a C/U‐rich loop to bind to a G‐rich sequence in the 5’UTR of its target mRNA tlpB ‐HP0102 (Pernitzsch et al., 2014, 2021), in structure and function.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In our recent work, we showed that processed CJnc190 encoded in the CJnc190/180 sRNA locus of C. jejuni strain NCTC11168 represses ptmG translation by base‐pairing with its G‐rich translation initiation region using a single‐stranded C/U‐rich sequence within its second stem‐loop (SL2; Figure 1a; Svensson & Sharma, 2021). We noticed that the mature CJnc190 sRNA resembles the H. pylori sRNA RepG, which also uses a C/U‐rich loop to bind to a G‐rich sequence in the 5’UTR of its target mRNA tlpB ‐HP0102 (Pernitzsch et al., 2014, 2021), in structure and function.…”
Section: Resultsmentioning
confidence: 99%
“…RepG is encoded as a stand‐alone sRNA that is transcribed from a single promoter and does not require processing for its expression or stability (Pernitzsch et al., 2014). In contrast, CJnc190 is transcribed as precursors from two promoters (P1 & P2), which are then processed by RNase III into the mature, stable, and/or active form of the sRNA (Svensson & Sharma, 2021; Figure 1a,b). In addition, an antisense RNA, CJnc180, is transcribed from the opposite strand of CJnc190 and antagonizes its regulation of ptmG .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations